Peraturan Delegasi dalam Sistem Peraturan Perundang-Undangan Indonesia - Fathorrahman Fathorrahman (Fakultas Hukum Universitas Islam Jember, 2018)
Delegation regulations are laws and regulations made by other institutions or authorities which are delegated from the legislature to the executive body. Another meaning of the delegation regulation is the implementing regulations of the Act. As an executor, this authority can occur if the authority is delegated from the law as the parent who gives the delegation. In the Indonesian legislative system, there are many forms and types of delegation regulations, both from the parent side that delegates and the rules that get delegates. Regulations on Regulations Delegates in the Indonesian legal system are still various forms and types. Both from the parent side that delegates and the rules that get delegates. And there are still regulatory delegations to institutions that are not authorized to make legislation, such as delegations to judicial institutions / bodies, even though the institution is an institution that does not have the authority to make a general binding regulation. Keywords : Regulation, Delegation, Regulatory System